A Method Proposal for Throughfall Measurement in Grassland at Plot Scale in Temperate Climate: ‘Interception Tubes’ - Demir, Gökben; Friesen, Jan; Filipzik, Janett; Michalzik, Beate; Hildebrandt, Anke (Frontiers in Earth Science, 2022)
While net precipitation entering the soil is commonly measured in the woody ecosystems, there is a lack of field measurements for herbaceous vegetation. Small canopy heights and fragile stem structures are the primary challenges for net precipitation sampling in grasslands under field conditions. We designed a new in situ device, "interception tubes", for throughfall sampling in temperate grasslands. The instrument allows a natural development of grass canopy and sampling at multiple locations. Although it does not by construction separate throughfall and stemflow, the dominant part of the collected water is throughfall. We tested the interception tubes for splash loss with a drip experiment. Next, we evaluated the tubes’ measurements in a field installation at 25 locations both with and without vegetation cover. Also, we used measurements of gross precipitation, canopy height and soil water content to check plausibility of the measurements. The experiment showed splash loss for the tubes is small (< 3%) for the typical rain drop size for growing season in the region, as well as for throughfall drops of lower falling velocity. In the uncovered period, splash corrected tubes’ measurements were generally smaller than classical funnel measurements. But the statistical model revealed that the slope of their relation is close to unity (0.92) when accounting for topography and was probably related to wind effects. During the covered period, grass height systematically reduced below canopy precipitation measured by the tubes, indicating that they can capture spatial canopy drip patterns under denser grass foliage. The canopy height also altered the wind effect on the tube measurements. As in forest ecosystems, below canopy precipitation patterns were temporally stable and smaller events increased the spatial heterogeneity. The measured below canopy precipitation was between 95% and 22% that above, and grass height amplified the loss. The soil water balance showed the tubes underestimated soil water input at peak grass height, which suggests enhanced occurrence of stemflow in tall grass. Despite the underestimation of stemflow, the interception tubes are a suitable method for estimating the canopy effect on throughfall patterns in temperate grasslands, and stemflow can be quantified by additional soil moisture measurements.